Brigatinib Dose Rationale in Anaplastic Lymphoma Kinase–Positive Non‐Small Cell Lung Cancer: Exposure–Response Analyses of Pivotal ALTA Study. (26th December 2020) - Gupta, Neeraj; Wang, Xiaohui; Offman, Elliot; Rich, Benjamin; Kerstein, David; Hanley, Michael; Diderichsen, Paul M.; Zhang, Pingkuan; Venkatakrishnan, Karthik
Abstract : Brigatinib is a kinase inhibitor indicated for patients with advanced anaplastic lymphoma kinase–positive non‐small cell lung cancer who progressed on or are intolerant to crizotinib. Approval was based on results from a randomized, dose‐ranging phase II study (ALK in Lung Cancer Trial of AP26113 (ALTA)). Despite an apparent dose–response relationship for efficacy in ALTA, an exposure–response relationship was not discernable using static models driven by time‐averaged exposure. However, exposure–response modeling using daily time‐varying area under the concentration curve as the predictor in time‐to‐event models predicted that increasing the dose of brigatinib (range, 30 mg once daily (q.d.) to 240 mg q.d.) would result in clinically meaningful improvements in progression‐free survival (PFS), intracranial PFS, and overall survival. Grade ≥ 2 rash and amylase elevation were predicted to significantly increase with brigatinib exposure. These results provided support for a favorable benefit‐risk profile with the approved dosing regimen (180 mg q.d. with 7‐day lead‐in at 90 mg) versus 90 mg q.d.